Correlation and co-localization of QTL for stomatal density, canopy temperature, and productivity with and without drought stress in Setaria - Prakash, Parthiban Thathapalli (Journal of experimental botany, 2021)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology.